Acid and alkali resistant lithium adsorption material as well as preparation method and application thereof

By using amino crown ether-polyurea structural framework in lithium adsorption materials and bonding amino-modified lithium ion sieve, the problems of low adsorption capacity and poor acid and alkali resistance caused by the shedding of lithium ion sieve are solved, and high adsorption capacity is achieved , excellent structural stability and strong hydrophilicity.

CN119488887AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311049692.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

The lithium-ion sieve of existing lithium adsorption materials is prone to fall off, resulting in low adsorption capacity, not resistant to strong acids and alkalis, and poor hydrophilicity.

Method used

The amino crown ether-polyurea structural framework is adopted, and a dispersed amino-modified lithium ion sieve is bonded into the framework to improve the structural stability and hydrophilicity of the material.

Benefits of technology

The adsorption capacity and magnesium lithium selectivity of lithium adsorbent materials are improved, the tolerance to the acid and alkali environment is enhanced, and the hydrophilicity of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488887A_ABST
    Figure CN119488887A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion adsorption materials, and discloses an acid and alkali resistant lithium adsorption material, which comprises a skeleton and an amino modified lithium ion sieve dispersed in the skeleton, the lithium ion sieve is connected with the framework through a structure as shown in a formula I; the framework comprises a structural unit A, a structural unit B and a structural unit C; the structural unit A and the structural unit C are connected through a structure as shown in a formula II; the structural unit B and the structural unit C are connected through a structure as shown in a formula III; at least one structure as shown in a formula IV, a formula V and a formula VI is formed among the structural units C; # imgabs0 # Ar1 is a residue of a polyamine; ar2 is a residue of a polyisocyanate; ar3 is a residue of an amino crown ether. The acid and alkali resistant lithium adsorption material has excellent structural stability, acid and alkali resistance and hydrophilic performance, so that the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion adsorption materials, and in particular to an acid- and alkali-resistant lithium adsorption material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the lithium battery industry, the demand for lithium resources in various industries is continuing to grow, and the importance of lithium production is also increasing. At present, lithium resources are mainly distributed in lithium ore and salt lake brine, but lithium ore resources are constantly decreasing and the development cost is increasing; in contrast, the lithium water resources in salt lake brine are low in cost and abundant in reserves. China is the largest lithium consumer country. Although it has abundant liquid lithium resources, extracting lithium from lithium water resources is a challenging task, so most upstream lithium source materials still rely on imports. The main methods for extracting lithium from salt lakes in China include adsorption, precipitation, extraction, electrodialysis, calcination, etc. Among them, the adsorption method has the advantages of simple process, green energy saving, and good selectivity. It is superior to other methods in terms of time and cost, and has broad application prospects. Since domestic salt lake brine generally has the problem of low lithium grade, the core of lithium extraction by adsorption method is to prepare highly selective adsorbents. Highly selective lithium extraction adsorbents mainly include ion sieve adsorbents and amorphous hydroxide adsorbents. These two types of adsorbents exist in powder form, which are easily lost in water bodies and difficult to recycle, and require specific molding methods such as granulation and film forming.

[0003] Due to their special structure, manganese and titanium lithium ion sieves have the best selective adsorption effect on lithium ions under alkaline conditions and the best desorption effect on lithium ions under acidic conditions. Therefore, the adsorbent particles prepared by granulation need to be resistant to acid and alkali. Common granulation methods include natural polymers such as sodium alginate and synthetic resins such as polyvinyl chloride. The adsorbent particles obtained by granulation methods such as sodium alginate are not resistant to acid and alkali. Although polyvinyl chloride is resistant to acid and alkali, it has poor hydrophilicity. Therefore, it is urgent to develop an adsorbent granulation product with high adsorption capacity, acid and alkali resistance and good hydrophilicity.

[0004] CN114011386A discloses a method for preparing lithium adsorption particles, which comprises mixing LiCl·2Al(OH)3·nH2O powder with polyol, diisocyanate, etc., and then further mixing with a binder and granulating, and removing the solvent to obtain lithium adsorption particles. However, the steps are complicated, secondary granulation is required, and the adsorption capacity is low. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems in the prior art that the lithium ion sieve in the lithium adsorption material is easy to fall off, resulting in low adsorption capacity, inability to resist strong acids and alkalis and poor hydrophilicity, and provide an acid- and alkali-resistant lithium adsorption material and a preparation method and application thereof. The acid- and alkali-resistant lithium adsorption material comprises an amino crown ether-polyurea polymer skeleton and an amino-modified lithium ion sieve dispersed in the skeleton. The amino-modified lithium ion sieve is bonded to the lithium adsorption material, so that the lithium ion sieve is not easy to fall off during long-term use. The acid- and alkali-resistant lithium adsorption material of the present invention comprises a specific structure, so that the lithium adsorption material has excellent structural stability, acid and alkali resistance and hydrophilicity, thereby improving the adsorption capacity and magnesium-lithium selectivity of the lithium adsorption material.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an acid-alkali resistant lithium adsorption material, wherein the lithium adsorption material comprises a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton;

[0007] The lithium ion sieve is connected to the framework via the structure shown in Formula I;

[0008]

[0009] The skeleton comprises structural unit A, structural unit B and structural unit C;

[0010] The structural unit A and the structural unit C are connected by the structure shown in formula II;

[0011]

[0012] The structural unit B and the structural unit C are connected by the structure shown in formula III;

[0013]

[0014] Ar1 is a residue of a polyamine; Ar2 is a residue of a polyisocyanate; and Ar3 is a residue of an amino crown ether.

[0015] A second aspect of the present invention provides a method for preparing an acid- and alkali-resistant lithium adsorption material, wherein the preparation method comprises the following steps:

[0016] (1) aminated the lithium ion sieve to obtain an amino-modified lithium ion sieve;

[0017] (2) mixing the amino-modified lithium ion sieve, polyamine and amino crown ether in water to obtain a mixed solution A;

[0018] (3) dropping an organic solution containing polyisocyanate into mixed solution A and stirring to obtain mixed solution B; after reaction, heat-treating the reaction product to obtain a semi-solidified cross-linked product; and extruding to obtain an acid- and alkali-resistant lithium adsorption material.

[0019] The third aspect of the present invention provides an acid and alkali resistant lithium adsorption material obtained by the above preparation method.

[0020] A fourth aspect of the present invention provides an application of the above-mentioned acid and alkali resistant lithium adsorption material in lithium extraction from salt lakes.

[0021] Through the above technical scheme, the acid and alkali resistant lithium adsorption material and the preparation method and application thereof provided by the present invention have the following beneficial effects.

[0022] The acid- and alkali-resistant lithium adsorption material provided by the present invention has an amino crown ether-polyurea structural skeleton including structural units A, B and C, and the amino-modified lithium ion sieve is dispersed in the skeleton in a bonded form, so that the bonded amino-modified lithium ion sieve is dispersed stably and is not easy to fall off from the lithium adsorption material.

[0023] Furthermore, the lithium ion sieves are sparsely bonded in the polyurea structural skeleton, so that there are more gaps in the middle of the lithium adsorption material, with a macroporous structure, and the polyurea structure -HNCONH- increases the hydrophilicity of the lithium adsorption material, which is beneficial to improving the adsorption capacity of lithium.

[0024] Furthermore, the structural unit B carries an amino crown ether residue, wherein the crown ether ring and the polyurea structural skeleton produce a synergistic effect, which can significantly improve the adsorption capacity, adsorption rate and magnesium-lithium selectivity of the acid-base resistant lithium adsorption material for lithium ions in the solution.

[0025] Furthermore, since the polyurea structure has a higher degree of cross-linking than the polyurethane structure, the structure is more stable; in addition, there are a large number of hydrogen bonds in the polyurea, which can promote the formation of a three-dimensional network structure of the skeleton. The strength of the polyurea structure is much greater than that of the polyurethane structure, which makes the lithium adsorption material more stable, which is beneficial to the adsorption and desorption of lithium in the lithium adsorption material under acidic and alkaline conditions, and reduces the damage of acid and alkali to the structure of the lithium adsorption material.

[0026] In the preparation method of the acid- and alkali-resistant lithium adsorption material provided by the present invention, a polyurea structure skeleton is formed by in-situ polymerization reaction between polyamines, amino crown ethers, and polyisocyanates, and an amino-modified lithium ion sieve is bonded to the skeleton by bonding, thereby avoiding the degradation of the performance of the lithium adsorption material due to the shedding of the lithium ion sieve during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Scanning electron microscope image of the lithium adsorption material prepared in Example 1.

[0028] Figure 2 Scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] In one aspect, the present invention provides an acid- and alkali-resistant lithium adsorption material, wherein the lithium adsorption material comprises a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton;

[0031] The lithium ion sieve is connected to the framework via the structure shown in Formula I;

[0032]

[0033] The skeleton comprises structural unit A, structural unit B and structural unit C;

[0034] The structural unit A and the structural unit C are connected by the structure shown in formula II;

[0035]

[0036] The structural unit B and the structural unit C are connected by the structure shown in formula III;

[0037]

[0038] Ar1 is a residue of a polyamine; Ar2 is a residue of a polyisocyanate; and Ar3 is a residue of an amino crown ether.

[0039] In the present invention, the acid- and alkali-resistant lithium adsorption material has an amino crown ether-polyurea structural skeleton including structural units A, B and C, and the amino-modified lithium ion sieve is dispersed in the skeleton in a bonded form, so that the bonded amino-modified lithium ion sieve is dispersed stably and is not easy to fall off from the lithium adsorption material.

[0040] Furthermore, the lithium ion sieves are sparsely bonded in the polyurea structural skeleton, so that there are more gaps in the middle of the lithium adsorption material, with a macroporous structure, and the polyurea structure (-HNCONH-) increases the hydrophilicity of the lithium adsorption material, which is beneficial to improving the adsorption capacity of lithium.

[0041] Furthermore, the structural unit B carries an amino crown ether residue, wherein the crown ether ring and the polyurea structural skeleton produce a synergistic effect, which can significantly improve the adsorption capacity, adsorption rate and magnesium-lithium selectivity of the acid-base resistant lithium adsorption material for lithium ions in the solution.

[0042] Furthermore, since the polyurea structure has a higher degree of cross-linking than the polyurethane structure, the structure is more stable; in addition, there are a large number of hydrogen bonds in the polyurea, which can promote the formation of a three-dimensional network structure of the skeleton. The strength of the polyurea structure is much greater than that of the polyurethane structure, which makes the lithium adsorption material more stable, which is beneficial to the adsorption and desorption of lithium in the lithium adsorption material under acidic and alkaline conditions, and reduces the damage of acid and alkali to the structure of the lithium adsorption material.

[0043] According to the present invention, the polyamine is selected from at least one of diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine.

[0044] In the present invention, when the above-mentioned specific type of polyamine is used, the polyurea skeleton containing its residue can be easily formed into a three-dimensional network structure, so that the stability of the lithium adsorption material is strong, which is beneficial to the adsorption and desorption of lithium by the lithium adsorption material under acidic and alkaline conditions, reduces the damage of acid and alkali to the structure of the lithium adsorption material, and has strong hydrophilicity, which is beneficial to improve the lithium ion adsorption rate and adsorption capacity.

[0045] Furthermore, the polyamine is polyethyleneimine and / or polyethylene polyamine.

[0046] According to a preferred embodiment of the present invention, the polyamine is a combination of polyethyleneimine and polyethylene polyamine. Preferably, the content of the structural unit A containing polyethyleneimine is 45wt%-65wt% based on the total weight of the structural unit A. The content range is calculated based on the mass of the raw material input corresponding to each polyamine.

[0047] According to the present invention, the weight average molecular weight of the polyethyleneimine or polyetheramine is 90,000-120,000 g / mol.

[0048] Furthermore, the weight average molecular weight of the polyethyleneimine or polyetheramine is 100,000-110,000 g / mol.

[0049] According to the present invention, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4, N,N'-bis(methoxymethyl)dithiopurine-12-crown-4, 4'-aminobenzo-15-crown-5-ether, 4',4"(5")-diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

[0050] In the present invention, when the amino crown ether is used, the magnesium-lithium selectivity of the acid- and alkali-resistant lithium adsorption material can be significantly improved.

[0051] Furthermore, the amino crown ether is diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

[0052] Furthermore, the amino crown ether is selected from diaminodibenzo-14-crown-4.

[0053] According to the present invention, Ar2 is selected from at least one of the structures shown below:

[0054]

[0055]

[0056] wherein R1 and R2 are each independently a methylene group, R3 is a C6-C9 straight chain alkylene group or a branched chain alkylene group, R4, R5 and R6 are each independently a C1-C2 alkyl group, R7 is a C1-C2 alkylene group, R8, R9 and R 10 are each independently selected from H or C1-C3 alkyl, R 11 An alkyl group selected from C1-C3.

[0057] According to a preferred embodiment of the present invention, Ar2 in the skeleton comprises Preferably, based on the total weight of the structural unit C, it comprises The content of the structural unit C is 50wt%-60wt%. The content range is calculated by the mass of the raw material input corresponding to each Ar2.

[0058] In the present invention, when Ar2 is the above-mentioned specific combination, the polyurea structure obtained by the acid- and alkali-resistant lithium adsorption material is more stable, which is beneficial to the adsorption and desorption of lithium by the lithium adsorption material under acidic and alkaline conditions, and reduces the damage of acid and alkali to the structure of the lithium adsorption material.

[0059] According to the present invention, based on the total weight of the acid and alkali resistant lithium adsorption material, the content of the amino-modified lithium ion sieve is 10wt%-37wt%, the content of the structural unit A is 11wt%-17wt%, the content of the structural unit B is 5wt%-10wt%, and the content of the structural unit C is 35wt%-70wt%.

[0060] In the present invention, when the content of each structure in the acid- and alkali-resistant lithium adsorption material meets the requirements of the present invention, a large number of hydrogen bonds exist in the amino crown ether-polyurea structural skeleton of the acid- and alkali-resistant lithium adsorption material, which can promote the skeleton to form a three-dimensional network structure, so that the lithium adsorption material has strong stability, is conducive to the adsorption and desorption of lithium by the lithium adsorption material under acidic and alkaline conditions, reduces the damage of acid and alkali to the structure of the lithium adsorption material, has strong hydrophilicity, and is conducive to improving the lithium ion adsorption rate.

[0061] In the present invention, the saturated adsorption capacity of the acid- and alkali-resistant lithium adsorption material is directly related to the amino-modified lithium ion sieve in the lithium adsorption material. It can be understood that the saturated adsorption capacities are comparable only when the content of the amino-modified lithium ion sieve is the same.

[0062] Furthermore, based on the total weight of the acid- and alkali-resistant lithium adsorption material, the content of the amino-modified lithium ion sieve is 20wt%-28wt%, the content of the structural unit A is 11wt%-14wt%, the content of the structural unit B is 5wt%-7wt%, and the content of the structural unit C is 55wt%-62wt%.

[0063] According to the present invention, the amino-modified lithium ion sieve is a lithium ion sieve modified by an aminosilane coupling agent.

[0064] In the present invention, the lithium ion sieve modified by aminosilane coupling agent is more conducive to the bonding of the lithium ion sieve in the skeleton and is not easy to fall off, so that the lithium adsorption material has high lithium ion adsorption capacity and magnesium-lithium selectivity.

[0065] According to the present invention, based on the weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.1wt%-2wt%.

[0066] Furthermore, based on the weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.5wt%-1.8wt%.

[0067] According to the present invention, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.

[0068] According to the present invention, the lithium ion sieve is a titanium-based ion sieve and / or a manganese-based ion sieve.

[0069] Further, the lithium ion screening is from Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of .

[0070] According to the present invention, the average particle size of the lithium ion sieve is 0.01-500 μm.

[0071] In the present invention, when the average particle size of the lithium ion sieve meets the requirements of the present invention, the polyurea structural skeleton and the amino-modified lithium ion sieve can play a better synergistic role, so that the obtained acid and alkali resistant lithium adsorption material has excellent acid and alkali resistance and adsorption performance.

[0072] Furthermore, the average particle size of the lithium ion sieve is 0.03-300 μm.

[0073] According to the present invention, the specific surface area of ​​the acid-alkali resistant lithium adsorption material is 5-80m 2 / g.

[0074] According to the present invention, the pore size of the acid and alkali resistant lithium adsorption material is 0.1-5 μm.

[0075] According to the present invention, the pore volume of the acid-alkali resistant lithium adsorption material is 5-80m 3 / g.

[0076] In the present invention, when at least one of the specific surface area, pore size, and pore volume of the lithium adsorption material meets the above characteristics, the acid- and alkali-resistant lithium adsorption material has a high adsorption capacity, strong magnesium-lithium selectivity, and a high adsorption rate, and the acid- and alkali-resistant lithium adsorption material has good structural stability.

[0077] Furthermore, the specific surface area of ​​the acid-alkali resistant lithium adsorption material is 15-35m 2 / g.

[0078] Furthermore, the pore size of the acid and alkali resistant lithium adsorption material is 1-3 μm.

[0079] Furthermore, the pore volume of the acid-alkali resistant lithium adsorption material is 25-55m 3 / g.

[0080] According to the present invention, the average particle size of the acid and alkali resistant lithium adsorption material is 0.01-3 mm.

[0081] In the present invention, the acid- and alkali-resistant lithium adsorption material can be regular and / or irregular in shape. When the average particle size of the lithium adsorption material meets the above definition, the polyurea structural skeleton and the amino-modified lithium ion sieve can play a better synergistic role, so that the obtained acid- and alkali-resistant lithium adsorption material has excellent acid- and alkali-resistant performance and adsorption performance.

[0082] Furthermore, the average particle size of the acid and alkali resistant lithium adsorption material is 1-1.5 mm.

[0083] According to the present invention, at 25° C., in pure water, the water absorption rate of the acid- and alkali-resistant lithium adsorption material is 0.1-2 g / g.

[0084] In the present invention, when the water absorption rate of the acid-base resistant lithium adsorption material in pure water at 25° C. satisfies the above range, it indicates that the lithium adsorption material has a rapid water exchange capacity and can improve the adsorption rate of lithium ions.

[0085] According to the present invention, at 25° C., in pure water, the volume swelling rate of the acid-alkali resistant lithium adsorption material is 2-10%.

[0086] In the present invention, when the volume swelling rate of the acid-base resistant lithium adsorption material in pure water at 25° C. satisfies the above range, it indicates that the volume swelling rate of the lithium adsorption material is small and has anti-swelling characteristics.

[0087] A second aspect of the present invention provides a method for preparing an acid- and alkali-resistant lithium adsorption material, wherein the preparation method comprises the following steps:

[0088] (1) aminated the lithium ion sieve to obtain an amino-modified lithium ion sieve;

[0089] (2) mixing the amino-modified lithium ion sieve, polyamine and amino crown ether in water to obtain a mixed solution A;

[0090] (3) dropping an organic solution containing polyisocyanate into mixed solution A and stirring to obtain mixed solution B; after reaction, heat-treating the reaction product to obtain a semi-solidified cross-linked product; and extruding to obtain an acid- and alkali-resistant lithium adsorption material.

[0091] In the present invention, a polyurea structure skeleton is formed by in-situ polymerization reaction between polyamines, amino crown ethers and polyisocyanates, and the amino-modified lithium ion sieve is bonded to the skeleton by bonding, thereby avoiding the degradation of the performance of the lithium adsorption material due to the shedding of the lithium ion sieve during long-term use.

[0092] According to the present invention, the lithium ion sieve is a titanium-based ion sieve and / or a manganese-based ion sieve.

[0093] Further, the lithium ion screening is from Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of .

[0094] In the present invention, there is no particular limitation on the source of the lithium ion sieve, which can be obtained commercially or prepared by itself. Preferably, the preparation of the lithium ion sieve comprises: ball milling, drying, roasting and acid washing of a mixture of a titanium source, a lithium source and an organic solvent in sequence to obtain a lithium ion sieve. Preferably, the molar ratio of the titanium source to the lithium source is 1:0.95-1.05. Preferably, the mass ratio of the combination of the titanium source and the lithium source to the organic solvent is 1:1.5-3. Preferably, the ball milling conditions include: a ball milling rate of 100-300rpm and a ball milling time of 2-6h. Preferably, the roasting conditions include: a roasting temperature of 700-900°C and a roasting time of 4-8h in an air atmosphere. Preferably, the acid is selected from hydrochloric acid and / or sulfuric acid. Preferably, the concentration of the acid is 0.01-1mol / L. Preferably, the washing time is 0.5-24h.

[0095] According to the present invention, the average particle size of the lithium ion sieve is 0.01-500 μm.

[0096] In the present invention, when the average particle size of the acid- and alkali-resistant lithium adsorption material meets the above definition, the polyurea structural skeleton and the amino-modified lithium ion sieve can play a better synergistic role, so that the obtained acid- and alkali-resistant lithium adsorption material has excellent acid- and alkali-resistant properties and adsorption properties.

[0097] Furthermore, the average particle size of the lithium ion sieve is 0.03-300 μm.

[0098] According to the present invention, the lithium ion sieve is modified by amino silane coupling agent.

[0099] In the present invention, when the lithium ion sieve modified by aminosilane coupling agent is used, it is more conducive to the lithium ion sieve to be bonded in the skeleton and not easy to fall off, so that the acid and alkali resistant lithium adsorption material has high lithium ion adsorption capacity and magnesium-lithium selectivity.

[0100] According to the present invention, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.

[0101] According to the present invention, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-2.

[0102] Furthermore, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-1.8.

[0103] According to the present invention, the conditions for the amino modification include: pH value of 1-3, reaction temperature of 40-95° C., and reaction time of 0.5-12 h.

[0104] According to the present invention, based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve is 10wt%-37wt%, the content of the polyamine is 11wt%-17wt%, the content of the amino crown ether is 5wt%-10wt%, and the content of the polyisocyanate is 35wt%-70wt%.

[0105] In the present invention, when the content of each component meets the above-mentioned limitations, the polymerized skeleton can form a three-dimensional network structure, which makes the lithium adsorption material more stable, is beneficial to the adsorption and desorption of lithium under acidic and alkaline conditions, reduces the damage of acid and alkali to the structure of the lithium adsorption material, and has strong hydrophilicity, which is beneficial to improve the lithium ion adsorption rate and adsorption capacity.

[0106] Furthermore, based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve is 20wt%-28wt%, the content of the polyamine is 11wt%-14wt%, the content of the amino crown ether is 5wt%-7wt%, and the content of the polyisocyanate is 55wt%-62wt%.

[0107] According to the present invention, the polyamine is selected from at least one of diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine.

[0108] In the present invention, when the above-mentioned polyamine is selected, the obtained polyurea skeleton is easy to form a three-dimensional network structure, which makes the lithium adsorption material more stable, is beneficial to the adsorption and desorption of lithium by the lithium adsorption material under acidic and alkaline conditions, reduces the damage of acid and alkali to the structure of the lithium adsorption material, and has strong hydrophilicity, which is beneficial to improve the lithium ion adsorption rate and adsorption capacity.

[0109] Furthermore, the polyamine is polyethyleneimine and / or polyethylene polyamine.

[0110] According to a preferred embodiment of the present invention, the polyamine is a combination of polyethyleneimine and polyethylene polyamine. Preferably, the mass ratio of the polyethyleneimine to the polyethylene polyamine is 1-1.5:1.

[0111] According to the present invention, the weight average molecular weight of the polyethyleneimine or polyetheramine is 90,000-120,000 g / mol.

[0112] Furthermore, the weight average molecular weight of the polyethyleneimine or polyetheramine is 100,000-110,000 g / mol.

[0113] According to the present invention, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4, N,N'-bis(methoxymethyl)dithiopurine-12-crown-4, 4'-aminobenzo-15-crown-5-ether, 4',4"(5")-diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6.

[0114] In the present invention, when the amino crown ether is used, the adsorption capacity, adsorption rate and magnesium-lithium selectivity of the acid-alkali resistant lithium adsorption material for lithium ions in the solution can be significantly improved.

[0115] Furthermore, the amino crown ether is diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

[0116] According to the present invention, the polyisocyanate is selected from at least one of m-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methylm-phenylene diisocyanate.

[0117] According to a preferred embodiment of the present invention, the polyisocyanate is a combination of 1,4-phenylene diisocyanate and 1,3-phenylene diisocyanate. Preferably, the mass ratio of 1,4-phenylene diisocyanate to 1,3-phenylene diisocyanate is 1:1.5-1.

[0118] In the present invention, in step (3), the content of polyisocyanate in the organic solution containing polyisocyanate is 35wt%-55wt%. There is no particular limitation on the type of organic solvent, and conventional organic solvents in the art can be used, such as one or more of n-hexane, dodecane, n-heptane, and alkane solvent oils (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).

[0119] Furthermore, the content of polyisocyanate in the polyisocyanate-containing organic solution is 25wt%-40wt%.

[0120] According to the present invention, the reaction conditions include: reaction temperature of 30-70° C., and reaction time of 5-60 min.

[0121] In the present invention, when the above reaction conditions are adopted, it is more conducive to the in-situ polymerization reaction between the components to form a polyurea structural skeleton, so that the prepared lithium adsorption material has a high adsorption capacity for lithium ions in the solution and a strong magnesium-lithium selectivity.

[0122] Furthermore, the reaction conditions include: reaction temperature of 30-50°C and reaction time of 10-30min.

[0123] According to the present invention, the heat treatment conditions include: the heat treatment temperature is 75-150° C., and the heat treatment time is 5-60 min.

[0124] Furthermore, the heat treatment conditions include: the heat treatment temperature is 80-120° C., and the heat treatment time is 10-30 min.

[0125] According to the present invention, the preparation method further comprises: eluting the acid- and alkali-resistant lithium adsorption material with an acidic solution.

[0126] In the present invention, the acid-alkali-resistant lithium adsorption material is an acid-alkali-resistant lithium adsorption material precursor, and the acid-alkali-resistant lithium adsorption material is washed with an acidic solution to make the Li + and H + Exchange to activate the precursor and obtain H-type lithium ion sieve, such as Li 1.33 Mn 1.67 O4 to H 1.33 Mn 1.67 O4, the obtained H-type lithium ion sieve has a specific adsorption effect on lithium ions.

[0127] According to the present invention, the acidic solution is selected from hydrochloric acid and / or sulfuric acid.

[0128] According to the present invention, the concentration of the acidic solution is 0.01-1 mol / L.

[0129] According to the present invention, the elution time is 0.5-24h.

[0130] The third aspect of the present invention provides an acid and alkali resistant lithium adsorption material obtained by the above preparation method.

[0131] A fourth aspect of the present invention provides an application of the above-mentioned acid and alkali resistant lithium adsorption material in lithium extraction from salt lakes.

[0132] The acid- and alkali-resistant lithium adsorption material of the present invention has high adsorption capacity for lithium ions in the solution, fast adsorption rate, strong magnesium-lithium selectivity, and is resistant to strong acids and alkalis and hydrophilic, and can meet the needs of lithium extraction from salt lakes.

[0133] The present invention will be described in detail below through examples.

[0134] Dynamic adsorption-desorption cycle method: The lithium adsorption material (4 g) obtained in the embodiment and the comparative example is placed in a glass column for acid washing. At 30°C, 0.5 M hydrochloric acid (200 mL) is pumped in at a flow rate of 2 BV / h using a peristaltic pump for 24 hours to wash and remove lithium ions in the material. Then, the lithium adsorbent to be tested is obtained after washing with deionized water until neutral. 500 mL of magnesium-lithium mixed solution (Li + The concentration is 100ppm, Mg 2+A mixed solution of lithium chloride and magnesium chloride with a concentration of 2000 ppm, pH = 9.5, 30°C) was adsorbed, and then 250 mL of 0.5 M hydrochloric acid was pumped in at a flow rate of 2 BV / h using a peristaltic pump for 8 hours for desorption to obtain a desorption solution, which was recorded as the first dynamic adsorption-desorption cycle.

[0135] Static adsorption-desorption cycle method: Take 0.5g of the lithium adsorption material to be tested and mix it with 40mL of lithium magnesium mixed solution (Li + The concentration is 100ppm, Mg 2+ Static adsorption was performed in a mixed solution of lithium chloride and magnesium chloride with a concentration of 2000 ppm, pH = 9.5, 30° C. After the concentration of lithium ions and magnesium ions in the lithium-magnesium mixed solution no longer changed, desorption was performed with 100 mL of 0.5 M HCl for 24 hours.

[0136] Determination of saturated adsorption capacity of lithium adsorbent material: adopt the above-mentioned static adsorption-desorption cycle method, when the static adsorption equilibrium of the lithium adsorbent material to be tested is reached, separate the lithium adsorbent material to be tested from the mixed solution, and calculate the saturated adsorption capacity Q according to the following formula.

[0137]

[0138] Wherein, Q is the saturated adsorption capacity, in mg / g, which reflects the adsorption amount of the lithium adsorbent material when the adsorption reaches equilibrium; C0 and C are the lithium ion concentrations at the initial and saturated adsorption of the lithium adsorbent material in the lithium-magnesium mixed solution, respectively, in mg / L; V is the volume of the lithium-magnesium mixed solution, in L; M is the mass of the lithium adsorbent material to be tested, in g.

[0139] The magnesium-lithium selectivity of the lithium adsorption material: The magnesium-lithium selectivity coefficient is calculated according to the following formula using the above-mentioned static adsorption-desorption cycle method. It refers to the priority of lithium adsorption materials for A ions when adsorbing A and B ions. The larger the value, the better the selectivity for A, which reflects the selectivity of lithium adsorption materials for different ions.

[0140]

[0141]

[0142] In the above formula, C0 is the concentration of each ion in the lithium-magnesium mixed solution, mg / L; C is the ion concentration when the lithium adsorption material to be tested is saturated with adsorption, mg / L; V is the volume of the lithium-magnesium mixed solution, mL; m is the mass of the lithium adsorption material to be tested, g. K A is the lithium ion distribution coefficient, K B is the magnesium ion partition coefficient.

[0143] Mass loss ratio of lithium adsorption material: the weighing method is adopted, that is, the mass of the lithium adsorption material before use (i.e., the initial mass) and the mass of the lithium adsorption material after 30 dynamic adsorption-desorption cycles are weighed respectively, and the ratio of the lost mass to the initial mass is the mass loss ratio.

[0144] The morphology of the lithium adsorption materials was characterized by scanning electron microscopy (SEM, S-4800).

[0145] The concentration of magnesium ions or lithium ions was measured by ion chromatography (ICS-1100, DIONEX, America).

[0146] The specific surface area, pore size and pore volume of lithium adsorption materials are determined by the BET method. The specific method is to determine the adsorption-desorption isotherm of lithium adsorption materials for N2 at 77K (the lithium adsorption material is degassed by heating and vacuuming to remove the impurity gas adsorbed on the surface. Then it is weighed and placed in liquid nitrogen. At liquid nitrogen temperature, the nitrogen adsorption amount of the sample is measured at different pre-set pressure points to obtain the adsorption isotherm), and the BET specific surface area, pore size and pore volume are obtained by fitting.

[0147] The average particle size of the lithium adsorbent material was measured by scanning electron microscopy.

[0148] In the lithium adsorption material, the content of the amino-modified lithium ion sieve and each structural unit is calculated by the feed ratio of the raw materials corresponding to each structural unit.

[0149] In the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is determined by a weight gain method.

[0150] Water absorption rate (A): The water absorption mass of the unit mass of the lithium adsorbent material to be tested in pure water at 25°C. The calculation formula is A=(W1-W0) / W0, unit g / g, where W0 is the mass of the lithium adsorbent material to be tested before immersion in pure water, and W1 is the mass of the lithium adsorbent material to be tested after immersion in water for 24 hours.

[0151] Volume expansion rate (P): The volume expansion rate of the unit mass of the lithium adsorption material to be tested in pure water at 25°C. The formula is P = (V1-V0) / V0, where V0 is the volume of the lithium adsorption material to be tested before immersion in pure water, and V1 is the volume of the lithium adsorption material to be tested after being immersed in pure water until the volume does not change.

[0152] The raw materials in the following preparation examples, embodiments and comparative examples are all commercially available products.

[0153] Preparation Example 1

[0154] Amino-modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:1. Hydrochloric acid was used to adjust pH = 2, and stirring was continued at 80°C for 6h to obtain amino-modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve A was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve A was 0.14wt%.

[0155] Preparation Example 2

[0156] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80℃, and 0.8g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:0.8. Hydrochloric acid was used to adjust pH=2, and the mixture was stirred continuously at 80℃ for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve B was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve B was 0.12wt%.

[0157] Preparation Example 3

[0158] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1.5g of γ-aminopropyltriethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:1.5. Hydrochloric acid was used to adjust pH=2, and the mixture was stirred continuously at 80°C for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Amino-modified lithium ion sieve C was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve C was 1.8wt%.

[0159] Preparation Example 4

[0160] Preparation of modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80℃, and 0.1g of γ-aminopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to aminosilane coupling agent was 1:0.1. Hydrochloric acid was used to adjust pH=7.5, and continuous stirring was performed at 120℃ for 12h to obtain amino-modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 4h and dried. Amino-modified lithium ion sieve D was obtained, and the content of aminosilane coupling agent in amino-modified lithium ion sieve D was 0.6wt%.

[0161] Preparation Example 5

[0162] Modified lithium ion sieve: Lithium ion sieve powder Li2TiO3 (0.1μm) was ground in a ball mill for 12h to improve dispersibility. 1g of ground powder was dissolved in 1L ultrapure water at 80°C, and 1g of mercaptopropyltrimethoxysilane was added to the system. The mass ratio of lithium ion sieve to coupling agent was 1:1. Hydrochloric acid was used to adjust pH=2, and continuous stirring was performed at 80°C for 6h to obtain a modified lithium ion sieve. The product was centrifuged at room temperature and then washed three times with pure water. Ball milled at room temperature for 6h and dried. Modified lithium ion sieve E was obtained, and the content of mercaptopropyltrimethoxysilane coupling agent in the modified lithium ion sieve E was 0.11wt%.

[0163] Example 1

[0164] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1:1);

[0165] (2) Under mechanical stirring, the same volume of 13 wt% Isopar E solution of 1,4-phenylene diisocyanate and 12 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 22.73 wt%, the content of the polyamine was 13.64 wt%, the content of the amino crown ether was 6.82 wt%, and the content of the polyisocyanate was 56.81 wt%). After reacting at 50°C for 10 min, heat treatment at 90°C for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0166] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 52wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0167] Example 2

[0168] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1:1);

[0169] (2) Under mechanical stirring, the same volume of 20 wt% Isopar E solution of 1,4-phenylene diisocyanate and 20 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 27.78 wt%, the content of the polyamine was 11.11 wt%, the content of the amino crown ether was 5.56 wt%, and the content of the polyisocyanate was 55.55 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.3 mm.

[0170] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0171] Example 3

[0172] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1.33:1);

[0173] (2) Under mechanical stirring, the same volume of 18 wt% Isopar E solution of 1,4-phenylene diisocyanate and 17 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 20.87 wt%, the content of the polyamine was 12.17 wt%, the content of the amino crown ether was 6.09 wt%, and the content of the polyisocyanate was 60.87 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with a particle size of 1.5 mm.

[0174] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 57wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 51.4 wt %; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0175] Example 4

[0176] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1:1);

[0177] (2) Under mechanical stirring, the same volume of 20 wt% Isopar E solution of 1,4-phenylene diisocyanate and 20 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 25.71 wt%, the content of the polyamine was 11.43 wt%, the content of the amino crown ether was 5.71 wt%, and the content of the polyisocyanate was 57.15 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-base resistant lithium adsorption material with an average particle size of 1.2 mm.

[0178] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0179] Example 5

[0180] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1.25:1);

[0181] (2) Under mechanical stirring, the same volume of 10 wt% Isopar E solution of 1,4-phenylene diisocyanate and 10 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 10.34 wt%, the content of the polyamine was 13.79 wt%, the content of the amino crown ether was 6.9 wt%, and the content of the polyisocyanate was 68.97 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0182] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 55.6wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0183] Example 6

[0184] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1.25:1);

[0185] (2) Under mechanical stirring, the same volume of 10 wt% Isopar E solution of 1,4-phenylene diisocyanate and 10 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 36.7 wt%, the content of the polyamine was 16.51 wt%, the content of the amino crown ether was 10.09 wt%, and the content of the polyisocyanate was 36.7 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0186] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 55.6wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0187] Example 7

[0188] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, stirring for 24 hours to obtain a mixed solution A (the mass ratio of polyethyleneimine to polyethylene polyamine is 1:1);

[0189] (2) Under mechanical stirring, the same volume of 9 wt% Isopar E solution of 1,4-phenylene diisocyanate and 9 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 48.28 wt%, the content of the polyamine was 3.45 wt%, the content of the amino crown ether was 17.24 wt%, and the content of the polyisocyanate was 31.03 wt%). After reacting at 50° C. for 10 min, heat treatment at 90° C. for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0190] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0191] Example 8

[0192] The acid and alkali resistant lithium adsorption material was prepared according to the method of Example 1, except that diaminodibenzo-14-crown-4 was replaced by 2-aminomethyl-15-crown-5.

[0193] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 50wt%; Ar3 is the residue of 2-aminomethyl-15-crown-5.

[0194] Example 9

[0195] The acid- and alkali-resistant lithium adsorption material was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced with an amino-modified lithium ion sieve B.

[0196] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 52wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0197] Example 10

[0198] The acid- and alkali-resistant lithium adsorption material was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced with an amino-modified lithium ion sieve C.

[0199] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 52wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0200] Embodiment 11

[0201] The acid and alkali resistant lithium adsorption material was prepared according to the method of Example 1, except that the modified lithium ion sieve A was replaced with amino-modified lithium ion sieve D.

[0202] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 52wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0203] Example 12

[0204] (1) Ultrasonic dispersion of amino-modified lithium ion sieve A in aqueous solution, adding polyethyleneimine (Mw = 100,000 g / mol), polyethylene polyamine and diaminodibenzo-14-crown-4, and stirring for 24 hours to obtain a mixed solution A;

[0205] (2) Under mechanical stirring, 25 wt% of Isopar E solution of 1,4-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 22.73 wt%, the content of the polyamine was 13.64 wt%, the content of the amino crown ether was 6.82 wt%, and the content of the polyisocyanate was 56.81 wt%). After reacting at 50°C for 10 min, heat treatment at 90°C for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0206] In the prepared skeleton, Ar1 is a residue of polyethyleneimine and polyethylene polyamine, wherein the content of the structural unit A containing polyethyleneimine is 50wt% based on the total weight of the structural unit A; Ar2 is Ar3 is the residue of diaminodibenzo-14-crown-4.

[0207] Example 13

[0208] (1) The amino-modified lithium ion sieve A is uniformly dispersed in an aqueous solution by ultrasonication, polyethyleneimine (Mw = 100,000 g / mol) and diaminodibenzo-14-crown-4 are added, and stirred for 24 hours to obtain a mixed solution A;

[0209] (2) Under mechanical stirring, the same volume of 13 wt% Isopar E solution of 1,4-phenylene diisocyanate and 12 wt% 1,3-phenylene diisocyanate was dripped into the mixed solution A to obtain a mixed solution B (based on the total weight of the amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 22.73 wt%, the content of the polyamine was 13.64 wt%, the content of the amino crown ether was 6.82 wt%, and the content of the polyisocyanate was 56.81 wt%). After reacting at 50°C for 10 min, heat treatment at 90°C for 10 min obtained a semi-solidified cross-linked product, which was extruded by an extruder to obtain an acid-alkali resistant lithium adsorption material with an average particle size of 1.2 mm.

[0210] In the prepared skeleton, Ar1 is a residue of polyethyleneimine; Ar2 is (Formula A) and Wherein, based on the total weight of the structural unit C, the content of the structural unit C comprising formula A is 52wt%; Ar3 is the residue of diaminodibenzo-14-crown-4.

[0211] Comparative Example 1

[0212] An acid and alkali resistant lithium adsorption material was prepared according to the method of Example 1, except that diaminodibenzo-14-crown-4 was not added, and based on the total weight of the amino-modified lithium ion sieve, the polyamine and the polyisocyanate, the content of the amino-modified lithium ion sieve was 22.73% by weight, the content of the polyamine was 16.32% by weight, and the content of the polyisocyanate was 60.95% by weight.

[0213] Comparative Example 2

[0214] The acid and alkali resistant lithium adsorption material was prepared according to the method of Example 1, except that unmodified lithium ion sieve Li2TiO3 was used.

[0215] Comparative Example 3

[0216] The acid-base resistant lithium adsorption material was prepared according to the method of Example 1, except that polyethyleneimine and polyethylene polyamine were not added in step (1). No formed material could be obtained.

[0217] Comparative Example 4

[0218] The aqueous solution of polyethyleneimine (Mw = 100,000 g / mol) and polyethylene polyamine was mixed with 13% by weight of 1,4-phenylene diisocyanate and 12% by weight of 1,3-phenylene diisocyanate in Isopag G solution, the reaction temperature was 50 ° C, and the reaction was 10 minutes to obtain a semi-solidified product. Then the obtained semi-solidified product was evenly mixed with diaminodibenzo-14-crown-4 and amino-modified lithium ion sieve A, and extruded after drying. Based on the total weight of amino-modified lithium ion sieve, polyamine, amino crown ether and polyisocyanate, the content of the amino-modified lithium ion sieve was 22.73% by weight, the content of the polyamine was 13.64% by weight, the content of the amino crown ether was 6.82% by weight, and the content of the polyisocyanate was 56.81% by weight.

[0219] Comparative Example 5

[0220] The acid and alkali resistant lithium adsorption material was prepared according to the method of Example 1, except that the amino-modified lithium ion sieve A in step (1) was replaced by modified lithium ion sieve E.

[0221] In the present invention, the contents of amino-modified lithium ion sieve, structural unit A, structural unit B, and structural unit C in the acid- and alkali-resistant lithium adsorption materials prepared in Examples 1-13, Comparative Examples 1-2, and 4-5 are shown in Table 1. The specific surface area, pore size, and pore volume average particle size of the lithium adsorption materials of Examples 1-13, Comparative Examples 1-2, and 4-5 are shown in Table 2. The test results of the water absorption rate, volume swelling rate, saturated adsorption capacity, magnesium-lithium selectivity coefficient, and mass loss ratio of the lithium adsorption materials of Examples 1-13, Comparative Examples 1-2, and 4-5 are shown in Table 3.

[0222] Table 1

[0223]

[0224] Table 2

[0225]

[0226]

[0227] Table 3

[0228]

[0229]

[0230] According to Table 3, the acid-alkali resistant lithium adsorption material obtained in Examples 1-13 has a mass loss ratio of less than or equal to 2% after 30 cycles of adsorption under alkaline conditions and desorption under acidic conditions, indicating that the acid-alkali resistant lithium adsorption material of the present invention has a stable structure and can tolerate acid and alkali conditions. The mass loss ratio of the lithium adsorption material obtained by using unmodified lithium ion sieve (Comparative Example 2) and by physical mixing (Comparative Example 4) is greater than 3%, indicating that the bonding effect of the amino-modified lithium ion sieve can effectively increase the stability of the lithium adsorption material and reduce the mass loss ratio. Comparative Example 3 did not use polyamine, and the obtained product could not be formed and could not be used for adsorption.

[0231] When the addition amount of the amino-modified lithium ion sieve is the same, the acid- and alkali-resistant lithium adsorption material of the embodiment has an increased magnesium-lithium separation selectivity and an increased adsorption capacity compared with the comparative example 1 which does not contain the amino crown ether structure, indicating that under the synergistic effect of the amino crown ether and the amino-modified lithium ion sieve, the acid- and alkali-resistant lithium adsorption material has a high adsorption capacity for lithium ions in the magnesium-lithium mixed solution and a strong magnesium-lithium selectivity.

[0232] When the addition amount of amino-modified lithium ion sieve is the same, the acid- and alkali-resistant lithium adsorption materials obtained in Examples 1 and 8-13 have a large water absorption rate and a small volume expansion rate, indicating that the material has strong hydrophilicity and will not swell and break due to water absorption, further indicating that the obtained material has strong stability.

[0233] Figure 1 This is a scanning electron microscope image of the lithium adsorption material of Example 1. It can be seen that the material is loose and porous, and the lithium ion sieve is evenly dispersed in the skeleton. Figure 2 This is a scanning electron microscope image of the lithium adsorption material prepared in Comparative Example 1. It can be seen that the structure of the lithium adsorption material is densely packed.

[0234] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0235] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An acid and alkali resistant lithium adsorption material, characterized in that: The lithium adsorption material includes a skeleton and an amino-modified lithium ion sieve dispersed in the skeleton; The lithium ion sieve is connected to the framework via the structure shown in Formula I; The skeleton comprises structural unit A, structural unit B and structural unit C; The structural unit A and the structural unit C are connected by the structure shown in formula II; The structural unit B and the structural unit C are connected by the structure shown in formula III; Ar1 is a residue of a polyamine; Ar2 is a residue of a polyisocyanate; and Ar3 is a residue of an amino crown ether.

2. The acid- and alkali-resistant lithium adsorption material according to claim 1, wherein: The polyamine is selected from at least one of diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine, preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, the weight average molecular weight of the polyethyleneimine or polyetheramine is 90,000-120,000 g / mol; Preferably, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4-ether, N,N'-bis(methoxymethyl)dithiopurine-12-crown-4, 4'-aminobenzo-15-crown-5-ether, 4',4"(5")-diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6, preferably diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5; Preferably, Ar2 is selected from at least one of the following structures: wherein R1 and R2 are each independently a methylene group, R3 is a C6-C9 straight chain alkylene group or a branched chain alkylene group, R4, R5 and R6 are each independently a C1-C2 alkyl group, R7 is a C1-C2 alkylene group, R8, R9 and R 10 are each independently selected from H or C1-C3 alkyl, R 11 An alkyl group selected from C1-C3.

3. The acid- and alkali-resistant lithium adsorption material according to claim 1 or 2, wherein: Based on the total weight of the acid- and alkali-resistant lithium adsorption material, the content of the amino-modified lithium ion sieve is 10wt%-37wt%, the content of the structural unit A is 11wt%-17wt%, the content of the structural unit B is 5wt%-10wt%, and the content of the structural unit C is 35wt%-70wt%; Preferably, based on the total weight of the acid- and alkali-resistant lithium adsorption material, the content of the amino-modified lithium ion sieve is 20wt%-28wt%, the content of the structural unit A is 11wt%-14wt%, the content of the structural unit B is 5wt%-7wt%, and the content of the structural unit C is 55wt%-62wt%.

4. The acid- and alkali-resistant lithium adsorption material according to any one of claims 1 to 3, wherein: The amino-modified lithium ion sieve is a lithium ion sieve modified by an aminosilane coupling agent; Preferably, based on the weight of the amino-modified lithium ion sieve, the content of the aminosilane coupling agent is 0.1wt%-2wt%; Preferably, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the lithium ion sieve is a titanium ion sieve and / or a manganese ion sieve; Preferably, the lithium ion selection is Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of; Preferably, the average particle size of the lithium ion sieve is 0.01-500 μm, preferably 0.03-300 μm.

5. The acid- and alkali-resistant lithium adsorption material according to any one of claims 1 to 4, wherein: The specific surface area of ​​the acid and alkali resistant lithium adsorption material is 5-80m 2 / g, preferably 15-35m 2 / g; Preferably, the pore size of the acid- and alkali-resistant lithium adsorption material is 0.1-5 μm, preferably 1-3 μm; Preferably, the pore volume of the acid-alkali resistant lithium adsorption material is 5-80m 3 / g, preferably 25-55m 3 / g; Preferably, the average particle size of the acid- and alkali-resistant lithium adsorption material is 1-3 mm, preferably 1-1.5 mm; Preferably, at 25° C., in pure water, the water absorption rate of the acid-alkali resistant lithium adsorption material is 0.1-2 g / g; Preferably, at 25° C., in pure water, the volume swelling rate of the acid- and alkali-resistant lithium adsorption material is 2-10%.

6. A method for preparing an acid- and alkali-resistant lithium adsorption material, characterized in that: The preparation method comprises the following steps: (1) aminated the lithium ion sieve to obtain an amino-modified lithium ion sieve; (2) mixing the amino-modified lithium ion sieve, polyamine and amino crown ether in water to obtain a mixed solution A; (3) dropping an organic solution containing polyisocyanate into mixed solution A and stirring to obtain mixed solution B; after reaction, heat-treating the reaction product to obtain a semi-solidified cross-linked product; and extruding to obtain an acid- and alkali-resistant lithium adsorption material.

7. The preparation method according to claim 6, wherein: In step (1), the lithium ion sieve is a titanium ion sieve and / or a manganese ion sieve; Preferably, the lithium ion selection is Li 1.33 Mn 1.67 O4, Li2TiO3, LiTi2O4 and Li4Ti5O 12 At least one of; Preferably, the average particle size of the lithium ion sieve is 0.01-500 μm, preferably 0.03-300 μm; Preferably, the lithium ion sieve is modified by amino silane coupling agent; Preferably, the aminosilane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the mass ratio of the lithium ion sieve to the aminosilane coupling agent is 1:0.5-2; Preferably, the conditions for the amino modification include: pH value of 1-3, reaction temperature of 40-95° C., and reaction time of 0.5-12 h.

8. The preparation method according to claim 6 or 7, wherein: In step (3), based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polyisocyanate, the content of the amino-modified lithium ion sieve is 10wt%-37wt%, the content of the polyamine is 11wt%-17wt%, the content of the amino crown ether is 5wt%-10wt%, and the content of the polyisocyanate is 35wt%-70wt%; Preferably, based on the total weight of the amino-modified lithium ion sieve, the polyamine, the amino crown ether and the polyisocyanate, the content of the amino-modified lithium ion sieve is 20wt%-28wt%, the content of the polyamine is 11wt%-14wt%, the content of the amino crown ether is 5wt%-7wt%, and the content of the polyisocyanate is 55wt%-62wt%; Preferably, the polyamine is selected from at least one of diethylenetriamine, tetraethylenepentamine, polyethylenepolyamine, polyethyleneimine and polyetheramine, preferably polyethyleneimine and / or polyethylenepolyamine; Preferably, the weight average molecular weight of the polyethyleneimine or polyetheramine is 90,000-120,000 g / mol; Preferably, the amino crown ether is selected from at least one of diaminodibenzo-14-crown-4, 1-aza-12-crown-4, N,N'-bis(methoxymethyl)dithiopurine-12-crown-4, 4'-aminobenzo-15-crown-5-ether, 4',4"(5")-diaminodibenzo-15-crown-5 ether, 2-aminomethyl-15-crown-5 and 4'-aminobenzo-18-crown-6, preferably diaminodibenzo-14-crown-4 and / or 2-aminomethyl-15-crown-5.

9. The preparation method according to any one of claims 6 to 8, wherein: The polyisocyanate is selected from at least one of meta-xylylene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylene diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylene diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl meta-phenylene diisocyanate; Preferably, the reaction conditions include: reaction temperature of 30-70°C, preferably 30-50°C; reaction time of 5-60min, preferably 10-30min; Preferably, the heat treatment conditions include: heat treatment temperature of 75-150°C, preferably 80-120°C; heat treatment time of 5-60 min, preferably 10-30 min.

10. The preparation method according to any one of claims 6 to 9, wherein: The preparation method further comprises: eluting the acid- and alkali-resistant lithium adsorption material with an acidic solution; Preferably, the acidic solution is selected from hydrochloric acid and / or sulfuric acid; Preferably, the concentration of the acidic solution is 0.01-1 mol / L; Preferably, the elution time is 0.5-24h.

11. Acid- and alkali-resistant lithium adsorption material obtained by the preparation method according to any one of claims 6 to 10.

12. Use of the acid-alkali resistant lithium adsorption material according to any one of claims 1 to 5 and 11 in extracting lithium from salt lakes.

Citation Information

Patent Citations

  • Method for preparing lithium adsorbent resin

    CN102631897A

  • Titanium lithium ion sieve inorganic composite adsorption lithium extraction material and preparation method thereof

    CN115069209A

  • Adsorption material for extracting lithium from salt lake brine as well as preparation method and application of adsorption material

    CN115463646A

  • Lithium ion adsorbents

    US20230241581A1

  • KR20190009692A